The N-Terminus of Vps74p Is Essential for the Retention of Glycosyltransferases in the Golgi but Not for the Modulation of Apical Polarized Growth in Saccharomyces cerevisiae - Hsu, Jia-Wei; Chang, Lin-Chun; Jang, Li-Ting; Huang, Chun-Fang; Lee, Fang-Jen S. (PloS one, 2013)
Vps74p is a member of the PtdIns(4)P-binding protein family. Vps74p interacts with Golgi-resident glycosyltransferases and the coat protein COPI complex to modulate Golgi retention of glycosyltransferases and with the PtdIns(4)P phosphatase Sac1p to modulate PtdIns(4)P homeostasis at the Golgi. Genetic analysis has shown that Vps74p is required for the formation of abnormal elongated buds in cdc34-2 cells. The C-terminal region of Vps74p is required for Vps74p multimerization, Golgi localization, and glycosyltransferase interactions; however, the functional significance of the N-terminal region and three putative phosphorylation sites of Vps74p have not been well characterized. In this study, we demonstrate that Vps74p executes multiple cellular functions using different domains. We found that the N-terminal 66 amino acids of Vps74p are dispensable for its Golgi localization and modulation of cell wall integrity but are required for glycosyltransferase retention and glycoprotein processing. Deletion of the N-terminal 90 amino acids, but not the 66 amino acids, of Vps74p impaired its ability to restore the elongated bud phenotype in cdc34-2/vps74Δ cells. Deletion of Sac1p and Arf1p also specifically reduced the abnormal elongated bud phenotype in cdc34-2 cells. Furthermore, we found that three N-terminal phosphorylation sites contribute to rapamycin hypersensitivity, although these phosphorylation residues are not involved in Vps74p localization, ability to modulate glycosyltransferase retention, or elongated bud formation in cdc34-2 cells. Thus, we propose that Vps74p may use different domains to interact with specific effectors thereby differentially modulating a variety of cellular functions.